Examining the internal capabilities on SMEs performance: the effects of environmental turbulence and innovation strategy - Muhammad Zulqarnain, Arshad (2019)
The Small and Medium-Sized Enterprises (SMEs) play a crucial part in country's economic growth like Pakistan. Sustaining the SMEs performance is significant and is still attracted the attention of many researchers, even today, it is still compelling due to the emerging global competition in the context of developing countries. The previous findings on the understanding of the complex relationships among factors influencing firm performance remain fragmented and unexplained. Therefore, the purpose of this study is to investigate the relationship between innovation capability, intellectual capital, absorptive capacity, and SMEs performance in Pakistan. Furthermore, the study intends to examine the moderating effect of environmental turbulence and innovation strategy. The study employed the resource-based view as the underpinning theory with two supporting theories, namely, dynamic capability theory and contingency theory. Data were collected from 479 textile SMEs operating in Pakistan using a cross-sectional study design through self- administered questionnaires. However, only 348 surveys were valid for further analysis. This study utilized the Partial Least Squares Structural Equation Modelling to establish the validity and reliability of the measurement model and to test each hypothesis. The outcomes of this study show that innovation capability, intellectual capital, and absorptive capacity have a significant influence on SMEs performance. The results also reveal that environmental turbulence moderates the relationship between innovation capability, intellectual capital, absorptive capacity, and SMEs performance. Furthermore, innovation strategy moderates the relationship between innovation capability, absorptive capacity, and SMEs but innovation strategy does not moderate the relationship between intellectual capital and SMEs performance. The outcome of this study provides new knowledge and valuable insights for government agencies, such as SMEs Development Authority to look further at the programmes and guidelines, and enforce new policies toward improving the performance of SMEs in Pakistan. The study also contributes to the theory as it extends the Resource-Based View theory, Dynamic Capabilities Perspective, and the Contingency Theory and integrating distinct literature streams about innovation capability, intellectual capital, absorptive capacity, environmental turbulence, and innovation strategy. Lastly, there are some limitations as this study is a cross-sectional, using single source of data and just focuses on the textile sector. Hence, future studies should be longitudinal, use multiple sources data and focus on other Pakistan manufacturing sectors.